Using AI for Job Hunt Success: Interactive Workshop for Resume Writing and Job Interview Preparation: Penelitian - Juwita Rahma; Muhammad Taufik Syastra; Arif Budimansyah Purba; Dedih; Ahmad Najib Mutawally; Ludovikus (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Indonesian youth face significant challenges in transitioning from education to employment, with unemployment rates among 20-24 year-olds reaching 17.02% in 2022. This community service program aimed to enhance employability among high school graduates and final-year students in West Karawang through innovative AI-powered career preparation training. The interactive workshop was conducted at Horizon Indonesia University using bilingual delivery methods combining English exposure with Indonesian explanations. Thirty participants engaged in hands-on practice using ChatGPT for resume enhancement and interview preparation via their personal smartphones. The program utilized structured prompting techniques, voice mode practice, and peer learning approaches to build both AI literacy and practical job search skills. Results demonstrated 100% completion rates for basic activities and over 90% success in advanced applications, with participants expressing significantly increased confidence in job preparation activities. Qualitative feedback revealed enhanced understanding of AI tool applications, improved motivation for English language learning, and greater awareness of professional skill development requirements. This technology workshop successfully increased the digital work readiness of young people and is worthy of widespread replication.